PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN HOTEL JS LUWANSA JAKARTA - Maulana Hasanudin; Salman Paludi (LPPM Universitas Asa Indonesia, 2017)
Purpose- This study aims to determine the Motivation and Leadership on Employee Performance at JS Luwansa Hotel Jakarta. This research was conducted by survey method for 1 month at JS Luwansa Hotel Jakarta Design/methology/approach-There are 2 independent variables namely Motivation and Leadership and the dependent variable is Employee Performance. Analytical methods used are multiple linear regression, partial test with test, correlation coefficient and coefficient of determination. Findings- Results of research by analyzing using SPSS 20 found that Motivation and Leadership have significant effect on performance both simultaneously and partially. Where the ability of variables Motivation and Work Environment simultaneously explain the performance is equal to 16,81%. The remaining 83,19% is explained by other variables which not mentioned in this research model. Originality – At this premise, this is useful for management to maintain motivation aspects and work environment, too.